Meat and colorectal cancer in Middle Eastern and North African countries: update of literature review - Meimouna Mint Sidi Deoula; Khaoula El Kinany; Zineb Hatime; Hanae Abir Boudouaya; Karima El Rhazi (Frontiers Media S.A., 2020)
Abstract Background This review discusses the findings from epidemiological studies that have examined the possible role of meat and colorectal cancer (CRC) risk in Middle Eastern and North African (MENA) countries. Methods We conducted a literature search in the PubMed, Clinical Trials, Google Scholar, Science Direct, and Cochrane databases for observational studies that investigated the association between meat and CRC risk in adults from the MENA region. Results Eleven studies were included in this review. For red meat overall, significant associations were found. Regarding beef meat intake, the study included found controversial results with OR = 0.18 (95% CI 0.03-0.09). A positive association was observed between chicken and CRC risk, at OR = 2.52 (95% CI 1.33-4.77) to OR = 4.00 (95% CI 1.53-10.41) to OR = 15.32 (95% CI 3.28-71.45). A significant association was observed between processed meat intake and CRC risk, OR = 9.08 (95% CI 1.02-80.58). Conclusion This is the first literature review which illustrated the association between meat consumption and CRC risk in MENA region. We concluded that these studies included in this review have been controversial and not sufficient to establish a clear relationship between CRC and meat consumption in the MENA region. Further studies are necessary to be carried out in this region, with a larger sample size and submit to rigorous criteria. This review will help researchers to improve the quality of future studies about the association between CRC and nutritional diet in general and meat in particular.